Pengaruh penambahan tepung kulit ari kedelai dan tepung wortel terhadap sifat fisikokimia dan sensori mie kering [Effect of the soybean husk and carrot flour addition on the physicochemical and sensory properties of dry noodles] - Prayitno, Sutrisno Adi; Utami, Dwi Retnaningtyas; Ningrum, Sugiyati; Patria, Domas Galih; Putri, Silvy Novita Antrisna; Puspita, Rizqa Arya; Niam, Muhammad Khoirun (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2023)
Noodles are generally made from wheat flour which is only high in carbohydrates. Meanwhile, noodle products are needed sholud have others nutritional compound that can be used as daily needs consumption. One of them is the utilization of soybean husk which has been only discardes or used as animal feed. The utilazation of soybean husk waste has not been widely used for the food products. Noodles product can be susbtituted for carrots which are rich ini vitamins and carotenoids. Between of them can be substituted into noodle product proccesed. The purpose of this study was to analyze dry noodle products on the effect of soybean epidermis and carrot flour addition on physicochemical and sensory properties. These dry noodles could be used for a healthy menu as an alternative to carbohydrates in rice. There are some previous study about the effect of soybean husk added to the making of biscuit and cookies products that increase status of nutrition, however it was rarely utilized to substitute on the noodle making. Hence, the aim of this study were to utilize of the soybean husk and to analyze dry noodle products on the effect of soybean husk and carrot flour addition on physicochemical and sensory properties. The method of this study was carried out using quantitatve descriptive with prameters analyzed were moisture content, rehydration power, swelling power, and elasticity as well assensory. While the sensory data were examined by the Kruskal Wallis test. The physicochemical analysis properties test results showed that significant differences in rehydration power, swelling power, and water content, while the product elasticity showed no significant difference. The rehydration power, swelling power, elasticity,and water content showed that 86.67-133.34%;10-20%; 29.80-48.21% and1.19-1.95%, respectively. Furthermore, the sensory test results showed that there were significant differences in aroma and taste, while no significant differences in color and texture. The evaluation sensory of color and texture showed sig>α (0.88>0.05; 0.62>0.05), it mean that there was no difference, while in aroma and taste there were differences with sig<α (0.01<0.05). It can be concluded that the addition of soybean husk and carrot flour had an effect on the chemicals and organoleptic properties of dry noodle. To distguise the aroma of soybean husk other ingredients such as ginger or can be added. Hence,, the further research was necessary conducted in order to obtain strongly attractive color and aroma in dry noodle and to get rid of the unpleasant aroma optimally.